models of muscle spindles: From traditional methods to 3D bioprinting strategies - Yuannan Kang; Deepak M. Kalaskar; Darren J. Player (Journal of Tissue Engineering, 2025)
Muscle spindles are key proprioceptive mechanoreceptors composed of intrafusal fibres that regulate kinaesthetic sensations and reflex actions. Traumatic injuries and neuromuscular diseases can severely impair the proprioceptive feedback, yet the regenerative potential and cell-matrix interactions of muscle spindles remain poorly understood. There is a pressing need for robust tissue-engineered models to study spindle development, function and regeneration. Traditional approaches, while insightful, often lack physiological relevance and scalability. Three-dimensional (3D) bioprinting offers a promising approach to fabricate biomimetic, scalable, and animal-free muscle spindle constructs with controlled cellular architecture. Various bioprinting techniques – including inkjet, extrusion, digital light projection and laser-assisted bioprinting – have been explored for skeletal muscle fabrication, but replicating intrafusal fibre complexity remains a challenge. A major challenge lies in bioink development, where biocompatibility, printability and mechanical strength must be balanced to support intrafusal fibre differentiation and proprioceptive function. Recent molecular insights into spindle anatomy, innervation and extracellular matrix composition are shaping biofabrication strategies. This review discusses the current state of muscle spindle modelling, the application of 3D bioprinting in intrafusal fibre engineering, key challenges and future directions.